Adherence to WHO guidelines on severe pneumonia management in children and its impact on outcome: an observational study at Jinka General Hospital in Ethiopia - La Vecchia, Adriano; Teklie, Bereket Gebremedhin; Mulu, Dagmawi Awoke; Toitole, Kusse Koirita; Montalbetti, Francesca; Agostoni, Carlo; Hessebo, Tesfayesus Tefera; Tsegaye, Ademe; Pietravalle, Andrea; Manenti, Fabio; Tognon, Francesca; Pisani, Luigi; et al. (Frontiers in Public Health, 2023)
Introduction Poor adherence to guidelines during empirical antibiotic prescription in low-income countries could increase antimicrobial resistance without improving outcomes. Revised World Health Organization (WHO) guidelines published in 2014 on childhood (2–59 months) pneumonia re-defined the classification of severe pneumonia and changed the first-line treatment. The adherence to WHO guidelines in southern Ethiopia at the hospital level is unknown. We sought to determine the adherence to WHO guidelines on severe pneumonia first-line treatment in children in an Ethiopian referral hospital and assess the impact of non-adherence on patient outcomes. Methods An observational study was conducted on all children (2–59 months) clinically diagnosed with severe pneumonia and admitted to the Pediatric Ward of Jinka Hospital from 1 June 2021 to 31 May 2022. Exclusion criteria included a known HIV infection, ongoing antibiotic treatment before the event not related to acute pneumonia, or any other severe bacterial infection, confirmed or suspected. Adherence to guidelines was defined as first-line treatment with ampicillin or benzylpenicillin and gentamicin at the recommended dose. We compared the patients treated adherently vs. non-adherently. For categorical variables, the chi-square or Fisher's exact test was used, while for continuous variables, the Mann–Whitney U-test was used. Multivariate logistic regression was used to evaluate the association between adherence and demographic and clinical characteristics. Results During the observational period, 266 patients were registered as having severe pneumonia with an age between 2 and 59 months. After excluding 114 patients due to missing charts or other exclusion criteria, a total of 152 patients were included in the analysis. Of these, 78 (51%) were girls with a median age of 10 months (IQR 7–14). Overall, 75 (49%) patients received therapy according to the WHO guidelines. Compared to patients treated adherently to the guidelines, patients not treated adherently had similar outcomes [median length of stay of 3 (IQR 3–5) and 4 (IQR 3–6) days], median duration of oxygen therapy of 2 (IQR 1–3) for both the groups, and self-discharge rates of 5% and 6.5%, respectively). Conclusion Adherence to the revised WHO guideline was limited and not associated with outcomes. Efforts should focus on reducing the gap between theory and practice.